Zooplankton: a valuable environmental indicator tool in reservoir ecology management? - Geraldes, Ana Maria (2018)
The trends in zooplankton community were assessed in response to variations in the trophic state and water quality, occurring in a shallow reservoir subjected to seasonal water level fluctuations. Concomitantly, various ratios were calculated: (1) the ratio of crustacean abundance to rotifer abundance (NCrust/NRot); (2) the ratio of large (>10 μg) cladoceran abundance to total cladoceran group abundance (NLarge-Clad/NClad); (3) The trophic state indices of rotifer abundance. The reservoir’s hydrological cycle was characterized by three regimes. The maximum level phase lasted from January to the beginning of June, the emptying phase existed between mid-June to the beginning of September and the minimum level phase lasted from mid-September to the beginning of the first autumn/winter rain events. The highest values of total phosphorus, soluble reactive phosphorus, nitrate, and ‘chlorophyll a’ were found during the minimum level phase. Rotifera was the most abundant taxa, except in summer and in autumn where Cladocera and Copepoda were dominant. Redundancy analysis (RDA) revealed a strong contribution of temperature, chlorophyll a, soluble reactive phosphorous and total phosphorous to the observed significant associations between the zooplankton assemblage and environmental variables. The ordination space defined by the first two RDA axes accounted for 84.2% of species–environment relations and represented 25.4% of the variation in species data. The ratio NCrust/NRot showed the higher role of rotifers in the zooplankton community in the low level phase; the ratio NLargeClad/NClad showed a decreasing trend in the abundance of largesized cladocerans for the same mentioned period. Therefore, these indices seem suitable to be used in reservoir management as rapid tools to evaluate the effects of environmental disturbances to reservoir ecological integrity.